Canine Visceral Leishmaniasis: Important Factors in Maintenance of the disease in the city of Mirassol D'Oeste-Mt (Revista Brasileira Multidisciplinar, 2011)
Visceral Leishmaniasis was initially considered a disease associated with rural areas, but due to various environmental changes such as deforestation, urbanization, intensive migration process and endemic areas expansion, this disease is affecting humans and animals in urban and rural areas. In Brazil, there are severe endemic and epidemic occurrences of Visceral Leishmaniasis. In recent years the disease has spread through several states that had no cases of infected people and animals. Canine Visceral Leishmaniasis coexists with the human disease in all known outbreaks, but is more prevalent in humans. In Mirassol D'Oeste, Mato Grosso, for six consecutive years, cases of sick people have been reported, including deaths. Several serologically positive dogs and the presence of the Visceral Leishmaniasis transmission vectors characterized the city as conducive to disease development. This work aimed at assessing the status of canine visceral leishmaniasis transmission in two sections of Mirassol D'Oeste city, where 38 canine blood samples were collected in each of them and tested by RIFI and ELISA tests. The number of seropositive dogs amounted to 15 animals, 8 living in Jardim São Paulo section and 7, in Planalto section. There were no significant differences between the number of infected dogs in the two sections (x2 = 0.058, p = 0.9712, df = 1). The socioeconomic characteristics examined are distinct and a visible difference in the housing and life quality of residents was also observed. Possibly, these factors may be influencing the maintenance of the disease in Mirassol D'Oeste.
Keywords: Leishmaniasis; Serological surveys; Mirassol D'Oeste.